2017
DOI: 10.1016/j.bjpt.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of perceived barriers to physical activity in the general adult population: a cross-sectional study

Abstract: HighlightsOur investigation has shown factors that influence physical activity.Lack of motivation, resources, social support and fear of injury are barriers.Socioeconomic level, marital status, education and others are predictors.The design not allowed to calculate a causal relationship between the variables.A representative sample of the residents of Barranquilla (Colombia), is a strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
100
5
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 21 publications
12
100
5
7
Order By: Relevance
“…Other studies, however, indicate socioeconomic status, marital status, educational level, and self-perceived health as factors that influence the motivation to perform physical exercise [25]. In fact, the practice of physical exercise is a complex and multidimensional behaviour determined by numerous biological, psychological, sociocultural, and environmental factors [26].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, indicate socioeconomic status, marital status, educational level, and self-perceived health as factors that influence the motivation to perform physical exercise [25]. In fact, the practice of physical exercise is a complex and multidimensional behaviour determined by numerous biological, psychological, sociocultural, and environmental factors [26].…”
Section: Introductionmentioning
confidence: 99%
“…Kruger et al, reported larger improvements in VO 2 peak (+2.9 mL/kg/min vs + 1.7 mL/kg/min) in those that complied with the intervention, suggesting that adherence to exercise is key to improving outcomes. However, several barriers to exercise (ie social economic status, age, time commitment, social support etc) have been reported in healthy populations and these barriers are amplified further in patients with CLD who have numerous additional barriers (Figure ). It would seem plausible that learning how to overcome these barriers is essential to maintain adherence to exercise interventions, yet the method in which to achieve this remains a challenge.…”
Section: Adherence To Exercisementioning
confidence: 99%
“…Kruger et al, 26 reported larger improvements in VO 2 peak (+2.9 mL/kg/min vs + 1.7 mL/kg/min) in those that complied with the intervention, suggesting that adherence to exercise is key to improving outcomes. However, several barriers to exercise (ie social economic status, age, time commitment, social support etc) have been reported in healthy populations 44…”
Section: Adheren Ce To E Xercis Ementioning
confidence: 99%
“…The FITT characteristic most commonly manipulated is “time” . In particular, high‐intensity interval training (HIIT) has become popular, not least because HIIT training tends to be of shorter duration and the most commonly cited barrier to exercise participation is a lack of time . However, HIIT also manipulates time and removal of a barrier to exercise, either perceived or real, may not translate to increased adherence.…”
Section: Introductionmentioning
confidence: 99%